A theoretical study to improve wire sag of ultra-long wire bond loops for 3D/MCM packaging. (November 2017) - Kung, Huang-Kuang; Hsieh, Chi-Lung
Abstract: An innovative theoretical model by altering cross section of gold wire is proposed to reinforce the wire sag stiffness of a wire bond that suffered low yield for the applications of 3-dimensional and multi-chip module (MCM) packaging. The flexural rigidity of a wire bond is found to be a function of the material properties in the moment of inertia of a bond wire. Suffice to say, if the moment of inertia of the bond wire can be raised, the associated sag deflection will be diminished. By manipulating the moment of inertia of the bond wire, the sag deflection of the wire bond can be regulated appropriately to avoid wire sag and even the wire sweep enigma. The ellipse-like cross section of a wire bond is applied as a numerical example to improve the wire sweep stiffness or wire sag stiffness in this study. The results show the sag deflection of a wire bond can be reduced significantly if the ellipse-like cross section is oriented in the preferred direction of flexural rigidity of a wire bond. Furthermore, a systematic study of matching design is performed to control wire sag and wire sweep for the wire bonding applications of overhang cross-stacked and step-stacked packaging. It shows that to use a single diameter of bonding wire in these complicate bonding environments of overhang stacked configurations is a favored possibility. The advantages shown from the theoretical study need to be implemented in further work in a production environment on current wire bonding equipment. Graphical abstract: An innovative method to improve wire sag on ultra-long wire bonding loops has been proposed to correlate the relationship between sag deflection, bond height, bond span and flexural rigidity of a wire bond. According to the prediction of the sag stiffness model, wire sag can be diminished substantially if the moment of inertia of wire can be reinforced properly. The increase in sag stiffness due to a geometry transformation of the cross section of bond wire can be further obtained in terms of "equivalent" wire diameter. By employing the proposed method, the semiconductor industry may achieve savings on gold wire of up to 39% by weight, without any compromise in sag stiffness of the wire bond, providing a method of forming the elliptical wire using production wire bonding equipment can be developed. Proposed methodology of equivalent sag stiffness reduces area measure of bond wire.